Smart learning using artificial intelligence: Ways to improve the process of teaching general education subjects in higher education (China's experience) - Xiaoyu Wang; Yan Li; Jing Yan (Russian Journal of Education and Psychology)
Background. The new wave of revolution in the field of information technology has posed many new challenges to higher education. In the context of the collision of traditional concepts of learning and modern technologies “artificial intelligence + learning”, a new model of smart learning has emerged. At the same time, the integration of artificial intelligence technologies into teaching has given rise to certain problems, the solution of which is urgent, and the main factor that helps to solve them is the formation of a quality level of teaching in the conditions of using SMART-technologies.